(untitled) (Journal of Asian Development Studies, 2023)
Like many other legal systems worldwide, the sophisticated language element of Pakistan’s legal register contains a substantial percentage of expressions borrowed from other linguistic traditions. In this study piece, using borrowed terms in Pakistani legal register speech is difficult. The country’s legal discourse’s historical continuity, accuracy, and clarity are significantly influenced by these language components, which are frequently taken from Latin, Persian, and English. Like many legal systems worldwide, the Pakistani legal register is characterized by a diverse linguistic fabric, with a large amount of terminology acquired from other languages. This research looks into the problem of explanatory borrowed legal speech among Pakistan’s Bar and Bench. We are focused on comprehending how little linguistic differences impact communication and how foreign legal terminology influences juries, attorneys, and the legal system. Additionally, the goal of this study is to explore the complex network of borrowed terms that are used in Pakistani law. These linguistic components are frequently drawn from Latin, Persian, and English and are crucial for evaluating the nation’s legal discourse’s accuracy, coherence, and historical continuity. This research examines and explains the problem of borrowed legal speech in Pakistani bench and bar talk. The study investigates the rationale behind adopting this borrowed terminology. It focuses on comprehending the language intricacies and the effects of foreign legal phrases on judges, legal practitioners, and legal procedures. The study clarified how incorporating foreign legal language impacts the communication techniques within the Pakistani legal community by thoroughly analyzing legal texts, court hearings, and professional communication. Insights into the consequences of borrowed legal language for professional identity, legal clarity, and Pakistan’s larger legal culture are provided by the analysis, which takes into account historical, cultural, and practical reasons that contribute to its predominance.